Ascorbic Acid Inhibits Liver Cancer Growth and Metastasis in vitro and in vivo, Independent of Stemness Gene Regulation - Wan, Jingjing; Zhou, Juan; Fu, Lu; Li, Yubin; Zeng, Huawu; Xu, Xike; Lv, Chao; Jin, Huizi (Frontiers in Pharmacology, 2021)
Experimental and clinical evidence has indicated that the natural product ascorbic acid (AA) is effective in preventing and treating various types of cancers. However, the effect of AA on liver cancer metastasis has not yet been reported. Cancer stem cells (CSCs) play pivotal roles in cancer metastasis. Here, we demonstrated that AA selectively inhibited the viability of both liver cancer cells and CSCs, reduced the formation of cancer cell colonies and CSC spheres, and inhibited tumor growth in vivo. Additionally, AA prevented liver cancer metastasis in a xenotransplantation model without suppressing stemness gene expression in liver CSCs. Further study indicated that AA increased the concentration of H2O2 and induced apoptosis in liver CSCs. Catalase attenuated the inhibitory effects of AA on liver CSC viability. In conclusion, AA inhibited the viability of liver CSCs and the growth and metastasis of liver cancer cells in vitro and in vivo by increasing the production of H2O2 and inducing apoptosis. Our findings provide evidence that AA exerts its anti-liver cancer efficacy in vitro and in vivo, in a manner that is independent of stemness gene regulation.